2001
DOI: 10.1002/jemt.1187
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic overview of crinoid regeneration

Abstract: Crinoids are well known for their striking regenerative potential and can rapidly and completely regenerate arms lost following self-induced or traumatic amputation. Thus they provide a valuable experimental model for investigation of the regenerative process from the macroscopic to the molecular level. In these last years we have studied in detail the overall process of arm regeneration in the comatulid Antedon mediterranea. This phenomenon can be described on the whole as a typical blastemal regeneration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 52 publications
(103 reference statements)
1
80
1
2
Order By: Relevance
“…Based on histological studies, Wood et al (Wood et al, 2008) suggested that unfed A. filiformis increases protein metabolism by the breakdown of muscle tissues to fuel increased energetic demands in response to seawater acidification. It is likely that enhanced catabolism and cell turnover/dedifferentiation of muscle tissues following traumatic amputation in brittlestars and crinoids is related to cell differentiation to produce stem cells to regenerate lost tissues rather that fueling calcification processes (Candia Carnevali and Bonasoro, 2001;Biressi et al, 2010). However, despite increased NH 4 + excretion rates, the present study could not demonstrate any changes in ratios between ADM and DM between pH treatments, which would have indicated an increased utilization of muscle tissue or other amino acid compounds as an energy source.…”
Section: Research Articlecontrasting
confidence: 72%
“…Based on histological studies, Wood et al (Wood et al, 2008) suggested that unfed A. filiformis increases protein metabolism by the breakdown of muscle tissues to fuel increased energetic demands in response to seawater acidification. It is likely that enhanced catabolism and cell turnover/dedifferentiation of muscle tissues following traumatic amputation in brittlestars and crinoids is related to cell differentiation to produce stem cells to regenerate lost tissues rather that fueling calcification processes (Candia Carnevali and Bonasoro, 2001;Biressi et al, 2010). However, despite increased NH 4 + excretion rates, the present study could not demonstrate any changes in ratios between ADM and DM between pH treatments, which would have indicated an increased utilization of muscle tissue or other amino acid compounds as an energy source.…”
Section: Research Articlecontrasting
confidence: 72%
“…Crinoids are known to possess a strong capacity for regeneration, and have been studied using a variety of crinoids, such as the sea lily M. rotundus [1,26] and the comatulid Antedon mediterranea [5]. Comatulids regenerate most of their organs and many studies have focused on arm regeneration [5].…”
Section: O Japonicus As a Model Species For Developmental And Regenementioning
confidence: 99%
“…Comatulids regenerate most of their organs and many studies have focused on arm regeneration [5]. Regeneration is dependent on the nervous system and goes through three main phases: a repair phase, an early regenerative phase and an advanced regenerative phase [5].…”
Section: O Japonicus As a Model Species For Developmental And Regenementioning
confidence: 99%
“…First, a growing amount of molecular information about the regeneration process is available. Echinoderms show nerve-dependent regeneration [2][3][4][5][6][7] , and regeneration in these organisms has been shown to involve growth factors. For example, the bone morphogenetic protein/transforming growth factor-β (BMP/TGFB)-signalling pathway has been shown to function in regeneration in brittlestars and crinoids 5,9,10 , the HOX-signalling pathway in brittlestars and seastars 6 , and the Ependymin pathway in the sea cucumber 7 .…”
mentioning
confidence: 99%
“…These molecular pathways are repeatedly encountered during regeneration throughout the animal kingdom 1 . Second, all of the classical cellular and molecular tools are available for these models: EST libraries, not to mention the complete genome of the sea urchin Strongylocentrotus purpuratus 8 , immunohistochemistry 4,6,9 , in situ hybridization 5,10 , real-time PCR 7,10 , microarrays 11 , proteomics and so on. Echinoderm models allow analysis both in vivo and in vitro (for example, cell and tissue explant cultures 12 ).…”
mentioning
confidence: 99%